Studi Pemanfaatan Limbah CO2 Menjadi CO2 Cair dengan Teknologi CO2 Purification di Indutri Baja - Wahyu Kartika (Jurnal Jaring SainTek, 2021)
Steel products are needed to support the development of the manufacturing industry and other strategic industries in Indonesia. The steel industry is one of the contributors to CO2 gas emissions, which contributes about 15 percent of greenhouse gases (GHG). PT. XYZ, which is one of the largest steel industries in Indonesia, produces CO2 waste from the reduction process in the exhaust gas by an average of 20 tons/hour to produce its steel. This study aims to utilize CO2 waste in exhaust gas into liquid CO2 so that its utilization  can reduce CO2 emissions to the environment. Waste minimization by PT. XYZ is by recycling CO2 waste into liquid CO2 with CO2  Purification technology. Liquid CO2  is useful in various industries such as the manufacture of carbonated beverages, food and  beverage preservation, and the welding industry. Waste minimization has resulted in a 10% reduction in CO2 emissions by an average  of 10%. The magnitude of this decrease is influenced by the limited production capacity and storage tank capacity. The results of the study also show that the variables that are considered for the use of CO2  emissions are the purity of CO2, raw gas CO2.